The office of Prime Minister - Carter, Byrum (Princeton legacy library., 2015)
Starting with an illuminating historical survey, Mr. Carter devotes the main portion of his hook to the position of the British Prime Minister since 1894, with emphasis on the realities of British politics today. The relations of the Prime Minister with the public, his party, the Cabinet, and Parliament are discussed, and the problem of public relations generally is fully taken into account. Professor Carter fills an important gap, and provides an authoritative and readable commentary on British political life. Originally published in 1955. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.